Combining geodiversity with climate and topography to account for threatened species richness - Tukiainen, Helena; Bailey, Joseph J.; Field, Richard; Kangas, Katja; Hjort, Jan (Wiley, 2016)
Improved understanding of threatened species diversity is important for long-term conservation planning and natural area management, especially under ongoing global change. Geodiversity – the diversity of earth surface materials, forms and processes – may be a useful biodiversity surrogate for conservation planning, as well as having conservation value itself. Links between geodiversity and species richness have been demonstrated; establishing whether geodiversity also relates to threatened species’ diversity and distribution patterns is a logical next step for conservation biology. We used four geodiversity variables (rock type richness, soil type richness, geomorphological diversity, hydrological diversity), in addition to four climatic and topographic variables, to account for threatened species diversity across 31 of Finland’s national parks. We also analyzed rarity-weighted richness (a measure of site complementarity) of threatened vascular plants, fungi, bryophytes, and all species combined. Our 1km2-resolution dataset included 271 threatened species from 16 major taxa. We modeled threatened species richness (raw and rarity-weighted) using boosted regression trees. Commonly used climatic variables, especially the annual temperature sum above 5°C, dominated our models, consistent with the critical role of temperature in this boreal environment. Importantly, geodiversity added significant explanatory power, improving our understanding of threatened species. Greater geodiversity was consistently associated with increased threatened species richness across taxa; the combined effect of geodiversity variables was greater still in the rarity-weighted richness analyses (except for fungi). Geodiversity measures correlated most strongly with 3 species richness (raw and rarity-weighted) of threatened vascular plants and bryophytes; such correlations were weakest for molluscs, lichens, and mammals. While it is well known that simple measures of topography improve biodiversity modeling and conservation practice, our results suggest that geodiversity data relating to geology, landforms, and hydrology are also worth including. This reinforces recent arguments that ‘conserving Nature’s stage’ is an important principle in conservation.